Penerapan Fatwa DSN MUI Tentang Murabaha Bilwakalah Di BMT Bina Ihsanul Fikri (BIF) Bugisan Yogyakarta - Mujib Rido (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2021)
The BMF KSPS BIF in its business is divided into two namely Baitul Maal (social business) and Business (Baitul Tamwil). This social business is engaged in collecting Zakat, Infaq and Sadaqah funds and mentoring them to eight ashnaf. The priority scale for poverty alleviation through productive economic programs and scholarships. Its business ventures are engaged in empowering the lower class economic community with intensification of BIT in conducting murabhah financing using the media of wakalah, sometimes murabaha contracts in BMT often precede wakalah contracts. The presence of media wakalah to members in murabaha financing in BMT BIF is not wise and not careful in doing murabaha contracts when wakalah. On April 1, 2000 (26 Dzulhijjah 1420) MUI fatwa No.04 / DSN-MUI / IV / 2000 stipulated that if BMT wanted to represent members to buy goods from third parties, the murabahah sale and purchase agreement must be made after the goods in principle became belongs to BMT. In other words, authorization (wakalah) from BMT to any member or third party must be done before the murabahah sale agreement takes place. In this study the author wants to know about how the application of murabaha financing when the time is carried out by BMT BIF to its members. And how is the suitability of Fatwa DSN Number 04 / DSN-MUI / IV / 2000 in implementing murabahah financing when it is at the Bugisan BMF BIT Yogyakarta.Keywords: Murabaha bil wakalah, BMT BIF, Fatwa DSN MUI.